Understanding foreign direct investment in Indonesia. Issue 1 (21st March 2016) - Gopalan, Sasidaran; Hattari, Rabin; Rajan, Ramkishen S.
Abstract : Purpose: This paper aims to examine the dynamics of foreign direct investment (FDI) inflows into Indonesia. It is interested specifically in analysing and deliberating on two important policy questions: First, are all kinds of FDI useful from a policy perspective and what does the existing data on FDI reveal about the type of FDI inflows into Indonesia? Second, does the existing data help understand the extent of de facto bilateral linkages between Indonesia and other countries? Design/methodology/approach: The paper offers an in-depth case study of Indonesia using extensive exploratory data analysis on FDI inflows into Indonesia. As discussed in the paper, the data investigation uses and reconciles available FDI data both from national and international sources to understand the usefulness of such data for policy analysis. Findings: A data investigation of the trends in different types of FDI flows reveals a discernible downward trend in the ratio of mergers and acquisitions (M&A)–FDI ratio over the years. The paper argues that from a sequencing perspective, while a medium-to-long-term framework encouraging both domestic and foreign Greenfield investments could help Indonesia regain its growth luster, in the near term much more attention needs to be paid to FDI inflows in the form of M&As. Further, reconciling FDI and M&A data might help identify the original sources of FDI flows because existing data are based on flow of funds rather than ultimate ownership. Practical implications: Since the Asian financial crisis, Indonesia has successfully embarked on a phase of economic and political transition post-Suharto, with the cornerstones of such a strategy being a process of greater democratisation and decentralisation. However, there have been growing concerns of economic growth stagnation in recent years. One of the policies to revive the economy's lustre adopted by the government has been to attract greater FDI inflows. In this light, this paper examines the dynamics of FDI into Indonesia and deliberates on what kinds of FDI policymakers should focus on attracting to restore the country's growth lustre. Originality/value: The question of whether a policy to attract FDI should be careful in distinguishing the kind of FDI it wants to attract has not been sufficiently addressed in the related literature. This paper provides a framework to understand the different macroeconomic policy implications of types of FDI and provides extensive data analysis to not only understand the types of FDI but also sources of bilateral FDI inflows to Indonesia by reconciling FDI and M&A data.